Finding food: Issues and challenges in using Geographic Information Systems to measure food access - Forsyth, Ann (2010)
A significant amount of travel is undertaken to find food. This paper examines challenges in measuring access to food using Geographic Information Systems (GIS), important in studies of both travel and eating behavior. It compares different sources of data available including fieldwork, land use and parcel data, licensing information, commercial listings, taxation data, and online street-level photographs. It proposes methods to classify different kinds of food sales places in a way that says something about their potential for delivering healthy food options. In assessing the relationship between food access and travel behavior, analysts must clearly conceptualize key variables, document measurement processes, and be clear about the strengths and weaknesses of data.